2001
DOI: 10.1128/cdli.8.6.1204-1212.2001
|View full text |Cite
|
Sign up to set email alerts
|

Modulation ofMycobacterium bovis-Specific Responses of Bovine Peripheral Blood Mononuclear Cells by 1,25-Dihydroxyvitamin D3

Abstract: (48) and Zairians living in Belgium (35) compared to control individuals with less pigmented skin, presumably due to diminished synthesis. Tuberculosis, likewise, is common among individuals with heavily pigmented skin that relocate from equatorial regions to higher latitudes, in part due to deficiencies in vitamin D synthesis within the skin (65). In addition, patients with untreated tuberculosis often have lower concentrations of 25(OH)D 3 in plasma than do healthy subjects, and tuberculosis tends to occur d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 65 publications
(47 reference statements)
1
40
1
1
Order By: Relevance
“…Lesions were most prominent in the lungs and lung-associated lymph nodes (i.e., mediastinal and tracheobronchial). As previously demonstrated (57,58), recall proliferation of PBMC from M. bovisinfected cattle in response to M. bovis PPD was primarily the result of proliferation by CD4 ϩ and ␥␦ TCR ϩ cells (Table 2). Differences in proliferative responses between challenge doses (i.e., 10 3 versus 10 5 CFU) were not detected; thus, data are presented as pooled analyses.…”
Section: Cd4supporting
confidence: 68%
See 1 more Smart Citation
“…Lesions were most prominent in the lungs and lung-associated lymph nodes (i.e., mediastinal and tracheobronchial). As previously demonstrated (57,58), recall proliferation of PBMC from M. bovisinfected cattle in response to M. bovis PPD was primarily the result of proliferation by CD4 ϩ and ␥␦ TCR ϩ cells (Table 2). Differences in proliferative responses between challenge doses (i.e., 10 3 versus 10 5 CFU) were not detected; thus, data are presented as pooled analyses.…”
Section: Cd4supporting
confidence: 68%
“…Peripheral blood mononuclear cells (PBMC) were isolated from buffy coat fractions of blood collected in 2ϫ acid-citrate-dextrose (9). Staining of PBMC with PKH67 was performed according to the manufacturer's instructions (Sigma) and as described elsewhere (56)(57)(58). Briefly, 2 ϫ 10 7 PBMC were centrifuged (10 min, 400 ϫ g), supernatants were aspirated, and cells were resuspended in 1 ml of the diluent provided in the PKH67 kit.…”
Section: Methodsmentioning
confidence: 99%
“…The suppression of antigen-specific and mitogenic bovine T-cell responses by 1,25-D 3 has previously been described (3), and a more recent study indicated that this inhibitory activity of 1,25-D3 was also to be found in cattle infected with M. bovis (48). We attempted to clarify this effect of 1,25-D 3 in our M. bovis-infected cattle by using a monoclonal antibody raised against the VDR as a receptor agonist.…”
Section: Vdr Ligation Down-regulates T-cell Responsesmentioning
confidence: 72%
“…Absorbances of standards, controls, and test samples were converted to nanograms per milliliter of nitrite by comparison with absorbances of sodium nitrite (Fisher Chemicals, Fair Lawn, N.J.) standards within a linear curve fit. In prior studies (54), N G -monomethyl-L-arginine (1.15 mM; equimolar to the amount of L-arginine in the culture medium; Calbiochem, La Jolla, Calif.), a competitive inhibitor of the enzyme nitric oxide synthase (NOS), was added to parallel cultures to verify that the nitrite produced was due to the activity of NOS.…”
mentioning
confidence: 99%